2014
DOI: 10.1016/j.nucmedbio.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic pathway activation enhances brown adipose tissue metabolism: A [18F]FDG PET/CT study in mice

Abstract: Objective Pharmacologic approaches to study brown adipocyte activation in vivo with a potential of being translational to humans are desired. The aim of this study was to examine pre- and postsynaptic targeting of adrenergic system for enhancing brown adipose tissue (BAT) metabolism quantifiable by [18F]fluoro-2-deoxyglucose ([18F]FDG) positron emission tomography (PET)/ computed tomography (CT) in mice. Methods A β3-adrenoreceptor selective agonist (CL 316243), an adenylyl cyclase enzyme activator (forskoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 34 publications
5
43
1
Order By: Relevance
“…Mirbolooki et al reported that WAT of rats shows an increase in 18 F-FDG uptake by a single dose of CL316,243 (15). In addition, Quarta et al treated mice with CL316,243 for 4 wk and observed an increase in inguinal WAT 18 F-FDG uptake along with elevations of UCP1 protein and peroxisome proliferator-activated receptor-g coactivator 1 mRNA expression (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirbolooki et al reported that WAT of rats shows an increase in 18 F-FDG uptake by a single dose of CL316,243 (15). In addition, Quarta et al treated mice with CL316,243 for 4 wk and observed an increase in inguinal WAT 18 F-FDG uptake along with elevations of UCP1 protein and peroxisome proliferator-activated receptor-g coactivator 1 mRNA expression (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies to date have been limited mostly to acute BAT activation. Although b3AR stimulation has recently been shown to increase 18 F-FDG uptake in WAT of rodents (15,16), whether the level of 18 F-FDG uptake has sufficient accuracy to faithfully represent the magnitude of WAT browning has not been properly investigated. If 18 F-FDG can be shown to be a reliable biomarker, PET/CT imaging may help foster the in vivo translation of recent molecular discoveries related to WAT browning and may provide insight on how obesity can be treated by modifying WAT metabolism.…”
mentioning
confidence: 99%
“…Since NE is a fundamental neurochemical messenger, its accurate regulation is of major importance. Thus, the NET, responsible for NE equilibrium in the synaptic cleft, is representing the reuptake site and considered to be involved in a variety of neurological/psychiatric disorders [1,2], but also plays a pivotal role in cardiovascular [1][2][3] and metabolic diseases [3][4][5]. Reduced NET levels go along with neurological disorders like major depression [6,7], Parkinson's disease (PD), Alzheimer's disease (AD) [8][9][10][11][12][13][14][15][16][17][18], and cardiovascular diseases such as hypertension, cardiomyopathy, and heart failure [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a dysfunction of the NE system was reported in Attention Deficit Hyperactivity Disorder (ADHD) [9,17,19], suicide [1,12,20], substance abuse (cocaine dependence) [16], and schizophrenia [10]. A more recent discovery is the involvement of the NET in diseases like diabetes and obesity, due to its presence in brown adipose tissue (BAT) and the proposed activation thereof via NE [4,5,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these investigative modalities depend only on morphological alterations and consequently most anomalies can only be detect at complex stages of ailment and diagnosis of in time infections and its discrimination from inflammation or other involvements can be tricky [5].…”
Section: Introductionmentioning
confidence: 99%